PENGARUH MODEL PEMBELAJARAN SYNECTICS TERHADAP KEMAMPUAN MENULIS PUISI BAHASA INDONESIA PADA SISWA KELAS V SDN 1 BANGKELEKILA’ KABUPATEN TORAJA UTARA - Nur Abidah Idrus; Yusnadi; Pala, Jefrianto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study was motivated by the issue of students’ low ability in writing poetry. The objectives of this research were: (1) to describe the implementation of the synectics learning model in fifth-grade elementary school students; (2) to determine students’ poetry writing skills before and after the application of the synectics learning model; and (3) to examine the effect of the synectics learning model on the poetry writing skills of fifth-grade students. This research employed a quantitative approach using an experimental method and a quasi-experimental design with the nonequivalent control group design type. The population of this study was all fifth-grade students at SDN 1 Bangkelekila’, consisting of two classes which also served as the sample: class V A and V B, with a total of 46 students. The sampling technique used was purposive sampling, with class V A as the experimental group and class V B as the control group. Data collection techniques included tests, observation, and documentation. The data were analyzed using descriptive and inferential statistical analysis with the Independent sample t-test. The results from the experimental class showed: (1) the learning process using the synectics model was implemented with a “fair” category in the first meeting and a “good” category in the second meeting; (2) students’ poetry writing ability improved after the implementation of the synectics learning model, as evidenced by higher post-test scores compared to pre-test scores; and (3) the synectics learning model had a significant effect on the poetry writing skills of fifth-grade students at SDN 1 Bangkelekila’, North Toraja Regency. It can be concluded that the application of the synectics learning model significantly impacts poetry writing ability and leads to improvement in students’ test results.